Cognitive change in breast cancer patients up to 2 years after diagnosis. (26th December 2022) - Lange, Marie; Lefevre Arbogast, Sophie; Hardy-Léger, Isabelle; Rigal, Olivier; Le Fel, Johan; Pistilli, Barbara; Petrucci, Jean; Lévy, Christelle; Capel, Aurélie; Coutant, Charles; Médeau, Laure; Lerebours, Florence; et al.
Abstract: Background: Using the large nationwide French, national, multicenter, prospective cancer and toxicities (CANTO) cohort, we assessed cognitive functioning change after cancer treatments in a subgroup of breast cancer (BC) patients. Methods: We included patients with newly diagnosed invasive stage I-III BC enrolled in the CANTO substudy focused on cognitive evaluation and healthy control women matched for age and education. Episodic and working memory, executive functions, processing speed, attention, self-report cognitive difficulties (SRCD), fatigue, anxiety and depression were assessed with neuropsychological tests and self-report questionnaires before treatment (baseline) and approximately 1 (year 1) and 2 years (year 2) after diagnosis. We used linear mixed models to study changes in cognition and tested the effect of adjuvant chemotherapy. Results: We studied 276 localized BC patients (62% chemotherapy) compared with 135 healthy controls (HC). After adjustment, patients had lower baseline working memory, processing speed, and attention scores than HC ( P  ≤ .001), and the difference remained statistically significant over follow-up for working memory and processing speed. Executive function scores were similar between groups at baseline but decreased at year 1 among patients compared with HC ( P change  = .006). This decrease in chemotherapy patients was statistically significant compared with HC scores ( P change  < .001). After adjustment, SRCD were similar between BC patients and HC at baseline but increased in patients after treatment at year 1 ( P change  = .002). Conclusions: Cognitive difficulties are an important concern in BC patients, starting at diagnosis. Cancer treatments induce executive function decline and SRCD, which decrease over follow-up.